Clinical study on the various therapeutic approaches towards the management of hepatic abscess in adults (International Journal of Biomedical and Advance Research, 2017)
Background and objectives: Hepatic abscess is a very common and significant health condition in developing countries including India. Alcohol consumption is one of the most important predisposing factors in causation of hepatic abscess followed by uncontrolled diabetes and immunosuppression. The aim of this study was to device a definitive protocol in the management of patients with liver abscess and to evaluate the different treatment option of liver abscess, amoebic or pyogenic in order to have some guidelines in our setting Material and methods: A hospital based prospective study was conducted between August 2014 to September 2016 in Bangalore medical and research institute (Victoria hospital and Bowring and Lady Curzon Hospital), Bangalore. The following study was done in a set of 50 patients diagnosed with liver abscess admitted in our hospital. After confirming the diagnosis, patients were exposed to different treatment modalities which consisted of medical management alone, USG guided Aspiration, Pigtail catheterization and exploratory laparotomy. Results: In our study majority of the patients (84%) were of amoebic liver abscess (ALA) and only 16% were of pyogenic liver abscess (PLA). Out of 50 patients 8 patients responded to drug therapy alone, 40 patients underwent ultrasound-guided aspiration and pigtail catheter placement and 2 patients were treated with CT guided aspiration. Open surgical method was excluded in our study. Conclusion: Image guided drainage is the best modality of treatment for liver abscess size >4cm in both pyogenic and amoebic liver abscess however in small size abscess medical management is equally good. Abscess cavity resolves better and has a lower recurrence rate in case of percutaneous catheter drainage than percutaneous needle aspiration.. Mortality was not observed in our series. Prompt diagnosis, aggressive medical treatment along with minimal intervention can keep the morbidity and mortality associated with this condition to a bare minimum.